Information, territory, and networks : the crisis and maintenance of empire in Song China - De Weerdt, Hilde Godelieve Dominique (Harvard East Asian monographs, 2015)
"Based on a close reading of responses to official records and derivatives and a mapping of literati networks, the book proposes that the twelfth-century geopolitical crisis in Song China resulted in a lasting literati preference for imperial restoration and unified rule. It reorients the debate about the social transformation and local turn of imperial Chinese elites"--Provided by publisher